2012
DOI: 10.1016/j.jet.2010.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Sustained positive consumption in a model of stochastic growth: The role of risk aversion

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Note that configuration (i) includes the situation where capital and consumption grow near zero even under the worst realization of the random shock. The existing literature on stochastic growth contains various sufficient conditions on preferences and technology under which the optimal policy satisfies configuration (i); see, among others, Brock and Mirman (1972), Chatterjee and Shukayev (2008), Mitra and Roy (2006, 2010) and Olson and Roy (2000).…”
Section: On the Concept Of Safe Stock For Consumption Maintenancementioning
confidence: 99%
See 3 more Smart Citations
“…Note that configuration (i) includes the situation where capital and consumption grow near zero even under the worst realization of the random shock. The existing literature on stochastic growth contains various sufficient conditions on preferences and technology under which the optimal policy satisfies configuration (i); see, among others, Brock and Mirman (1972), Chatterjee and Shukayev (2008), Mitra and Roy (2006, 2010) and Olson and Roy (2000).…”
Section: On the Concept Of Safe Stock For Consumption Maintenancementioning
confidence: 99%
“…It has been shown that in this case consumption and capital fall below any strictly positive level infinitely often with probability one, no matter how large the initial stock (Mitra and Roy 2007). While it is easy to see that configuration (ii) can arise if the marginal productivity at zero is sufficiently small relative to the discount rate, Mirman and Zilcha (1975) presented an example to show that the optimal policy may lead to configuration (ii) even if the marginal productivity is infinite at zero for all realizations of the random shock; Mitra and Roy (2010) develop necessary and sufficient conditions for this phenomenon and relate it to the nature of risk aversion displayed by the utility function.…”
Section: On the Concept Of Safe Stock For Consumption Maintenancementioning
confidence: 99%
See 2 more Smart Citations
“…In most cases results show differences in the optimal policies when the objective function is no longer the expected value. Interest in understanding the effects of risk aversion in finance and economics has increased significantly in the last years, specially in dynamic models (see, for example, Blomvall and Shapiro (2006);Denuit et al (2006); Mitra and Roy (2012); Riedel (2004)). In this paper, risk aversion is represented by the Conditional Value-at-Risk (CVaR), a risk measure widely used in finance that was popularized by Rockafellar and Uryasev (2000).…”
mentioning
confidence: 99%